Tropical seaweed farming trends, problems and opportunities : focus on kappaphycus and eucheuma of commerce - Hurtado, Anicia Q.; Critchley, Alan T.; Neish, Iain C. (Springer, 2017)
This book collates the latest information on Kappaphycus and Eucheuma seaweeds. The edited volume provides an important companion to anyone studying or working with what is the world's largest cultivated marine plant biomass. The contributing authors have excelled in providing information on production and present and future uses of these carrageenan-bearing seaweeds. Important elements of taxonomy, distribution and methods of cultivation and processing are presented to the reader in an accessible and easily understood format. The book provides a number of valuable opinions on value addition and MUZE technologies which highlight value-chains associated with these important red algae.
Includes index.
Keywords: Marine algae culture.; Marine algae industry.; elektronické knihy; electronic books